2010
DOI: 10.1007/7854_2010_67
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroimaging Research in Bipolar Disorder

Abstract: Functional neuroimaging techniques have been important research tools in the study of bipolar disorder (BPD). These methods provide measures of regional brain functioning that reflect the mental state at the time of scanning and have helped to elucidate both state and trait features of BPD. This chapter will review converging functional neuroimaging evidence implicating state and trait dysfunction in a ventral prefrontal cortex-amygdala neural system in BPD. Emerging evidence that suggests a developmental prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 82 publications
4
7
0
Order By: Relevance
“…We observed reductions in the GM volume in the ventral PFC, particular within medial orbitofrontal cortex (OFC) (BA11), in SAs across mood disorders and within each diagnosis. This region of OFC plays an essential role in emotion regulation processes implicated in the emotion symptoms of both BD and MDD (Blond and Blumberg, 2011;Monkul et al, 2007;Morgan et al, 1993). The finding is consistent with previous studies of suicide behavior in BD or in MDD that showed GM volume reduction in this region in SAs (Benedetti et al, 2011;Monkul et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We observed reductions in the GM volume in the ventral PFC, particular within medial orbitofrontal cortex (OFC) (BA11), in SAs across mood disorders and within each diagnosis. This region of OFC plays an essential role in emotion regulation processes implicated in the emotion symptoms of both BD and MDD (Blond and Blumberg, 2011;Monkul et al, 2007;Morgan et al, 1993). The finding is consistent with previous studies of suicide behavior in BD or in MDD that showed GM volume reduction in this region in SAs (Benedetti et al, 2011;Monkul et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Decreases in dlPFC GM were observed in SAs with BD and MDD; however, the hemispheric laterality of the findings differed in the two disorders. It is possible this reflects the greater right hemisphere abnormalities associated with manic and left with depressive symptoms (Blond and Blumberg, 2011;Blumberg et al, 2003) and may relate to differing characteristics of attempters between the disorders. Within MDD, reductions in WM FA were also observed in the area of the left dlPFC in the SAs compared to the NSAs.…”
Section: Discussionmentioning
confidence: 99%
“…This ICD approach also revealed abnormalities in the LN and insula that are implicated in BD and have shown some other types of findings, although more limited than PFC findings in BD 5 . Increased LN ICD and seed‐based FC connectivity in the BD AYA ‐depressed group, provides novel information about LN dysfunction in BD depression.…”
Section: Discussionmentioning
confidence: 81%
“…Many studies have limited region of interest (ROI) approaches investigating similar regions, which could lead to overlooking additional key regions. Functional dysconnectivity is increasingly implicated; however, prior functional connectivity (FC) studies made assumptions about involved regions 5–7 . The many functional domains affected in BD, from sleep and activity to emotion and cognitive processes, implicate widely distributed abnormalities 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation